Dual-Mode Circular Polarization Selective Surface Cell for Single-Layer Dual-Band Circularly Polarized Reflectarray - Zheng Liu; Xue Lei; Jun-Mo Wu; Zhi-Jian Xu (International Journal of Antennas and Propagation)
A dual-mode circular polarization selective surface (CPSS) cell based on a modification of the Pierrot cell is presented for single-layer dual-band circularly polarized (CP) reflectarray antenna design. To achieve dual-mode CP discrimination performance, the improved three-dimensional geometry and the high-order resonances of the CPSS cell are utilized. The required phase shifts in both modes are obtained by varying the cell rotation angle. A single-layer dual-band reflectarray operating with orthogonal CPs has been fabricated and tested. Measured results show the peak gains of 25.2 dBi at 11.6 GHz with 31% 3 dB axial ratio (AR) bandwidth and 26.5 dBi at 14.6 GHz with 32% 3 dB AR bandwidth, respectively. The measured efficiency is 41.2% at 11.6 GHz and 55.5% at 14.6 GHz.